Foodservice tendencies and tourists’ lifestyle: new trends in tourism - Sarmento, E.; Loureiro, S.; Martins, R. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2017)
Food and catering are an ever-changing industry that influences, and it is influenced by the lives of millions of people in the world. The products and services provided by this business are constantly adapting to the influencing variables that are on-growing. Actually, consumers create the tendencies and are incredibly demanding on what they want and do not want. Tourists as consumers seek products that can adapt to your lifestyle. Therefore, in the foodservice field, restaurants are required to adapt to different variables, such as specific diets and trendy new tastes, while keeping their own characteristics. In addition, the numerous social media platforms have changed this industry completely. Restaurants have to focus on the new technology-savvy generations. This study seeks to understand the impact that the lifestyle changes from the last years and the Web 2.0 had in the field. Who creates the tendencies? Why and how are restaurants and food distributors adapting to the new needs of the market? In order to answer these questions, the 2015 and 2016 tendencies for the foodservice fields are analyzed. Findings help destination and restaurants managers to adapt and change their products and service.